(untitled) (Innovaciones Educativas, 2021)
This paper systematizes the results of the research by means of which one identifies the way in which the project-based learning strategy can contribute to the development of the statistical culture. This with regard to the dispersion measures of the student body in a rural context and who are in the eleventh grade at the San Isidro Educational Institution, located in Colombia. This research was developed under a qualitative approach and in accordance with the guidelines of participatory action research. First, the literature that theoretically addresses, among other topics, the teaching of statistics, dispersion measures, statistical culture and project-based learning is reviewed. Then, according to the methodological design, a diagnosis is made that showed the need to implement the PBL (Project-Based Learning) pedagogical strategy to address the issue of dispersion measures, in the search for use, interpretation and critical argumentation. As for the execution of the PBL, it takes place in the midst of social isolation and, therefore, the procedure in the classroom is redesigned for work activities at home. The results of this process, allowed the conclusion that, although significant achievements were made in terms of the development of a project and data management, due to situations such as social isolation, the expected levels of statistical culture were not reached. This situation leaves a greater reflection that, when implementing this type of strategies, the interaction of the student with his/her classmates and the constant communication with the teacher is essential.